Do Sublime - Marta Várzeas (Classica Digitalia: Autores Gregos e Latinos: textos, 2015)
Comes from the 10th century the oldest codex with the treatise On the Sublime. For a long time attributed to Cassius Longinus (third century ), the text is now generally considered a first century work, written by an anonymous or a Dionysius Longinus whose life and work is unknown. Ignored, as it seems, in Antiquity and the Middle Ages, the text came to meet its editio princeps only in 1554, in Basel and by the hand of Francesco Robortello. It was then successively edited and translated, first into Latin and later into several European languages, starting with the famous French version of Boileau that for a long time was the main source for the knowledge of the treatise in Europe. Peri Hypsous moves away from the stylistic approach of ancient rhetorical books and presents a definition of Sublime as a quality of discourse which produces in the hearers and readers not persuasion but wonder and ecstasy. It is precisely this idea of wonder and shudder that has inspired the works of Burke (A Philosophical Enquiry into the origin of our Ideas of the Sublime and Beautiful, 1757) and Kant, by whose hands the treatise On the Sublime entered the history of Western Aesthetics.